Demographic Security Of The State As An Integral Part Of Its Economic Security (Eurasian Journal of Humanities and Social Sciences, 2024)
This article is devoted to the definition of theoretical issues of demographic security of the state as the most important component of its economic security and the study of theoretical and practical issues of ensuring demographic security of the Republic of Uzbekistan at the present stage.